Lincoln's White House secretary : the adventurous life of William O. Stoddard - Stoddard, William O., 1835-1925 (Southern Illinois University Press, 2007)
William Osborn Stoddard, Lincoln's "third secretary" who worked alongside John G. Nicolay and John Hay in the White House from 1861 to 1865, completed his autobiography in 1907, one of more than one hundred books he wrote. An abridged version was published by his son in 1955 as "Lincoln's Third Secretary: The Memoirs of William O. Stoddard." In this new, edited version, Lincoln's White House Secretary: The Adventurous Life of William O. Stoddard, Harold Holzer provides an introduction, afterword, and annotations and includes comments by Stoddard's granddaughter, Eleanor.